2010
DOI: 10.1088/0004-637x/721/1/431
|View full text |Cite
|
Sign up to set email alerts
|

DUST EVOLUTION IN PROTOPLANETARY DISKS AROUND HERBIG Ae/Be STARS—THESPITZERVIEW

Abstract: In this paper we present mid-infrared spectra of a comprehensive set of Herbig Ae/Be stars observed with the Spitzer Space Telescope. The signal-to-noise ratio of these spectra is very high, ranging between about a hundred and several hundreds. During the analysis of these data we tested the validity of standard protoplanetary dust models and studied grain growth and crystal formation. On the basis of the analyzed spectra, the major constituents of protoplanetary dust around Herbig Ae/Be stars are amorphous si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
250
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 161 publications
(273 citation statements)
references
References 55 publications
17
250
6
Order By: Relevance
“…The Herbig AeBe sources in this sample have spectral type between F4 to B9 and are not embedded in large molecular clouds. They have been studied previously at mid-IR wavelengths by Spitzer (Juhász et al 2010) and the selected sample contains mostly nearby and low-luminosity sources. The T Tauri stars consist of an inhomogeneous sample of bright sources with K-G spectral type.…”
Section: Samplementioning
confidence: 99%
“…The Herbig AeBe sources in this sample have spectral type between F4 to B9 and are not embedded in large molecular clouds. They have been studied previously at mid-IR wavelengths by Spitzer (Juhász et al 2010) and the selected sample contains mostly nearby and low-luminosity sources. The T Tauri stars consist of an inhomogeneous sample of bright sources with K-G spectral type.…”
Section: Samplementioning
confidence: 99%
“…In Fig. 3 we compare the calculated peak position and FWHM for compact spherical grains (Mie scattering) and the distribution of hollow spheres (DHS; Min et al 2003) model with a filling factor f max = 1, which was found to be a good model for the crystalline silicate grains producing features in the Spitzer IRS wavelength regime (5-35 μm) (Juhász et al 2010). The temperature range covered is 50-295 K and the data is based on the results by Suto et al (2006).…”
Section: Effects Of Grain Shapementioning
confidence: 99%
“…To compare the results of our analysis of the Herschel spectra with those of the forsterite emission bands seen in the Spitzer observations, we use the spectra published by Juhász et al (2010) and Olofsson et al (2009). For the targets where we detected a 69 μm band, and those with marginal Spitzer detections, we carefully re-reduced the Spitzer spectra, using the same data reduction approach as Juhász et al (2010), but with the latest calibration version (S18.18.0). Our re-processed spectra only marginally differ from those reported by Juhász et al (2010) and Olofsson et al (2009).…”
Section: Comparison To Spitzer Irs Datamentioning
confidence: 99%
See 2 more Smart Citations